Mathematical Model for Transmission and Control of Covid-19. - Epasu, Simon (Kabale University, 2024)
Mathematical models have been used to study the transmission and control of previous infectious disease outbreaks such as the 1918 influenza pandemic, the 2002-2004 SARS epidemic, and the 2014-2016 Ebola outbreaks. The lessons learned from these outbreaks have informed the development and application of models for COVID-19. Mathematical models have been used to study the transmission and control of previous infectious disease outbreaks such as the 1918 influenza pandemic, the 2002-2004 SARS epidemic, and the 2014-2016 Ebola outbreaks. The lessons learned from these outbreaks have informed the development and application of models for COVID-I9. The general objective of this study is to develop and analyze a mathematical model for the transmission and control of COVID-19.